Making Policies Work: First- and Second-order Mechanisms in Policy Design - M Ramesh (Edward Elgar Publishing, 2019)
Policy design efforts are hampered by inadequate understanding of how policy tools and actions promote effective policies. The objective of this book is to address this gap in understanding by proposing a causal theory of the linkages between policy actions and policy effects. Adopting a mechanistic perspective, the book identifies the causal processes that activate effects and help achieve goals. It thus offers a powerful analytical tool to both scholars and practitioners of public policy seeking to design effective policies.